Lipid and Inflammatory Cardiovascular Risk Worsens Over 3 Years in Youth With Type 2 Diabetes: The TODAY clinical trial (American Diabetes Association, 2013)
OBJECTIVE: Type 2 diabetes increases cardiovascular risk. We examined lipid profiles and inflammatory markers in 699 youth with recent-onset type 2 diabetes in the TODAY clinical trial and compared changes across treatment groups: metformin alone (M), metformin plus rosiglitazone (M+R), and metformin plus intensive lifestyle program (M+L). RESEARCH DESIGN AND METHODS: Multiethnic youth with type 2 diabetes received M, M+R, or M+L. Statin drugs were begun for LDL cholesterol (LDL) ≥130 mg/dL or triglycerides ≥300 mg/dL. Lipids, apolipoprotein B (apoB), LDL particle size, high-sensitivity c-reactive protein (hsCRP), homocysteine, plasminogen activator inhibitor-1 (PAI-1), and HbA(1c) were measured over 36 months or until loss of glycemic control. RESULTS: LDL, apoB, triglycerides, and non-HDL cholesterol (HDL) rose over 12 months and then stabilized over the next 24 months. Participants with LDL ≥130 mg/dL or using LDL-lowering therapy increased from 4.5 to 10.7% over 36 months, while 55.9% remained at LDL goal (<100 mg/dL) over that time. Treatment group did not impact LDL, apoB, or non-HDL. Small dense LDL (particle size, ≤0.263 relative flotation rate) was most common in M. Triglycerides were lower in M+L than M, and M+L attenuated the negative effect of hyperglycemia on triglycerides and HDL in females. hsCRP, PAI-1, and homocysteine increased over time. However, hsCRP was lower in M+R compared with M or M+L. CONCLUSIONS: Dyslipidemia and chronic inflammation were common in youth with type 2 diabetes and worsened over time. Diabetes treatment, despite some treatment group differences in lipid and inflammatory marker change over time, is generally inadequate to control this worsening risk.